Examination of the differences in ethical perceptions between accounting and non-accounting students in Singapore. - Lee, Megan Hui Yi. (2008)
This paper seeks a greater understanding as to whether there are differences in ethical values between the accounting and non-accounting students (business and engineering). We have also explored the differences in ethical values in terms of gender and it appears that female students display a higher level of ethical perceptions than male students.